Feasibility Study for a Curriculum Comparison in Vocational Education and Training. Intermediary Report I: The 20 Top Performers - Ursula Renold; Thomas Bolli; Katherine Caves; Ladina Rageth; Vipul Agarwal; Filippo Pusterla (ETH Zurich, KOF Swiss Economic Institute, 2015)
Despite improved access to all educational levels, many countries around the world struggle with integrating young people into the labor market. The 2007 economic crisis exacerbated the problem, but not all countries were affected in the same way. This led to a vivid debate about how education and employment systems can and should be linked. Countries with well-developed vocational education and training (VET) systems seem to be better off in terms of their youth labor market situations. This raises the question of how countries should organize and design their VET curricula so that their youth make a smooth transition from education to employment. The Center on International Education Benchmarking (CIEB) has set the goal to analyze the world's most successful education systems. The objective is to compare the top-performing countries' instructional systems and identify their different approaches to education. Against this backdrop, the CIEB is supporting a comparative study of VET curricula, which are one fundamental component of any education system. However, such an international comparison of VET curricula faces many challenges, resulting mainly from the large variation in how national education systems train vocational and technical qualifications. In addition, VET curricula are not fully comparable due to different national political, economic, cultural, and institutional frameworks. Consequently, the CIEB mandated the KOF Swiss Economic Institute at the ETH Zurich to conduct a Feasibility Study that first defines a common strategy for tack-ling these challenges. Hence, this Feasibility Study aims to reduce the comparability problem to the furthest possible extent. The feasibility study consists of three phases, of which this intermediary report is the product of the first. This first phase addresses the following question: "Which countries can be identified as top-performing countries that should be included in the VET curricula comparison?" This report presents our findings on four main topics essential for achieving the goal of a feasibility study for the comparison of VET curricula. The first section explains our theoretical and conceptual approaches to the problem. These form the foundation of our strategy for identifying 20 top-performing countries with regard to VET, which is addressed in the second section. The third section presents the selected top-performing countries in brief portraits, which highlight not only their performance but also provide background information on VET governance. Finally, we compare and discuss these top-performing countries with regard to our performance criteria. Finally, this intermediary report concludes with the important findings for the second phase of the project.
Keywords: 330; Berufsbildung; Lehrplan; Jugendarbeitslosigkeit; Berufsbildungspolitik; Performance-Messung; Welt